Characterization of Pseudomonas Species Isolated from the Rhizosphere of Plants Grown in Serozem Soil, Semi-Arid Region of Uzbekistan - Dilfuza Egamberdiyeva (The Scientific World Journal)
Collections of native Pseudomonas spp. are kept at the NCAM of Uzbekistan. Some of those organisms were isolated from the rhizosphere of cotton, wheat, corn, melon, alfalfa, and tomato grown in field locations within a semi-arid region of Uzbekistan. Strains used for this study were Pseudomonas alcaligenes, P. aurantiaca, P. aureofaciens, P. denitrificans, P. mendocina, P. rathonis, and P. stutzeri. Some of the pseudomonads have been characterized in this report. These strains produced enzymes, phytohormone auxin (IAA), and were antagonist against plant pathogenic fungi in in vitro experiments. Most of the strains were salt tolerant and temperature resistant. Some of the Pseudomonas spp. isolated in this study have been found to increase the growth of wheat, corn, and tomato in pot experiments.